Influence of stacking sequence on mechanical properties of areca-kenaf fiber- reinforced polymer hybrid composite - Sathyaseelan P; Prabhukumar Sellamuthu; Lakshmanan Palanimuthu (Journal of Natural Fibers, 2022)
Hybrid laminates made using natural fibers have been finding applications in diverse fields such as automotive parts, building structures and sports goods. These laminates incorporate the benefits of the reinforcements used in constructions. The present work deals with the fabrication of hybrid laminate comprising of the natural fibers areca and kenaf in varying stacking sequences through the hand layup method. Epoxy resin (LY556) and hardener (HY951) are mixed in the ratio of 10:1 to prepare the matrix material. Six different hybrid laminates having five layers of areca and kenaf in different stacking sequences are produced. Two more laminates having either kenaf or areca in all the five layers and are produced to act as reference laminate. The prepared laminates are cut as per ASTM standards and subjected to tensile, compressive, flexural, impact and hardness tests in order to identify the properties of the fabricated laminates. The result shows that composite made with kenaf fiber as skin material and areca as core materials exhibit better tensile, flexural and hardness properties. Likewise, composites with outer layers of areca and core layers of kenaf fibers have high compressive and impact strength. The fractured surfaces after the mechanical tests are investigated through the Scanning Electron Microscope (SEM).